Football frenzy - Alex, Ko (UK : Usborne Books, 2011)
"Simple text invites the reader to find items hidden in American football-themed photographs"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Picture puzzles -- Juvenile literature; Football -- Juvenile literature